Hipereaktivitas Bronkus pada Pasien Gagal Jantung - Santi R Dewayanti (The Indonesian Heart Association, 2011)
Incidence of paroxysmal dyspnea accompanied by wheezing and coughing is a typical picture of congestive heart failure (congestive heart failure/CHF) formerly known as cardiac asthma. The symptoms are also present in bronchial asthma induced by the stimulus nonspecific bronchial hypereactivity.Bronchial Hypereactivity (BHR) is a wide bronchial constriction and bronchoconstriction response that gives rise to a variety of inhaled stimuli. Hypereactivity is characteristic of bronchial inflammation in asthma and is associated with the degree of severity of asthma. The intensity of the inflammation associated with airway sensitivity, airway wall thickness and airway reactivity. Airway obstruction in heart failure is clinically according to the classical picture of cardiac asthma.The presence of obstructive defects on spirometry showed lung function impairment in CHF. Functional sign of airway constriction is a reduction of the FVC FEV1 ratio, forced expiratory flow from different levels of FVC, airway obstruction on clinical heart failure according to the classical picture of cardiac asthma.Structural changes in the dam, especially bronchial, bronchial arteries and bronchial wall thickening of the bronchial hypereactivity role in non-allergic stimuli obtained in patients with CHF. Spirometry showed a decrease FEV1 and FEV1/FVC ratio. Abnormal results to be the cause of shortnessof breath which is the most frequent symptom in CHF.